(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Ukraine in the rating of the global index of innovations shows a deterioration of indicators both in general and in terms of sub-indices. The reasons for this in 2023 were martial law; the outflow of qualified personnel due to the war, loss of housing, job; increased level of danger; deterioration of the ecological condition in the country. The reasons for the deterioration can be considered martial law; the outflow of qualified personnel due to the war, loss of housing, job; increased level of danger; deterioration of the ecological situation in the country. The article analyzes the number of Internet, cellular and social network users among the population of Ukraine from 2019 to 2023. The authors argue that the technologies already available in the country, the level of business innovation, access to the Internet, and cellular coverage will have a significant impact on the post-war recovery of Ukraine’s economy. It is the quality of the Internet and access to it that is the foundation for the formation of digital entrepreneurship and the development of virtual businesses. The authors are convinced that a country’s tendency to be competitive depends on a number of determinants, in particular, the mechanisms of intellectual property rights used, the interaction between the use of intellectual property rights and the size and innovation of companies, available human capital, and the intensity of research and development.